The role of sex and weight on rituximab clearance and serum elimination half-life in elderly patients with DLBCL. - Muller, C.; Murawski, N.; Wiesen, M. H.; Held, G.; Poeschel, V.; Zeynalova, S.; Wenger, M.; Nickenig, C.; Peter, N.; Lengfelder, E.; Metzner, B.; Rixecker, T.; et al. (Blood, 2012)
Pharmacokinetics of 8 doses of rituximab (375 mg/m(2)) given in combination with 2-week cyclophosphamide, hydroxydaunorubicin, vincristine, and prednisone/prednisolone (CHOP-14) was determined by ELISA in 20 elderly patients with diffuse large B-cell lymphoma (DLBCL) 10 minutes before and after each infusion and 1 week and 1, 2, 3, 6, and 9 months after the last infusion. Population pharmacokinetic modeling was performed with nonlinear mixed-effect modeling software (NONMEM VI). Concentration-time data were fitted into an open 2-compartment model and total clearance, central compartment volume, intercompartment clearance, and volume of distribution at steady-state (Vd(ss)) were investigated. Total clearance was 9.43 mL/h and Vd(ss) was 9.61 l. Rituximab clearance was reduced (8.21 mL/h vs 12.68 mL/h; P = .003) and elimination half-life was prolonged in women compared with men (t(1/2beta) = 30.7 vs 24.7 days; P = .003). Body weight also affected Vd(ss) (0.1 l increase of Vd(ss) per kilogram above median of 75 kg). A sex-dependent effect and the higher weight of males contribute to their faster rituximab clearance, which might explain why elderly males benefit less from the addition of rituximab to CHOP than females. This trial was registered on www.clinicaltrials.gov as numbers NCT00052936, EU-20243 (RICOVER-60 Trial), EU-20534, and NCT00726700 (Pegfilgrastim Trial).
Keywords: Aged; Antibodies, Monoclonal, Murine-Derived/administration & dosage/*pharmacokinetics/*therapeutic use; Antineoplastic Combined Chemotherapy Protocols/*therapeutic use; Body Weight; Computer Simulation; Cyclophosphamide/therapeutic use; Doxorubicin/therapeutic use; Female; Humans; Lymphoma, Large B-Cell, Diffuse/*drug therapy/metabolism; Male; Middle Aged; Models, Biological; Prednisone/therapeutic use; Rituximab; Sex Factors; Treatment Outcome; Vincristine/therapeutic use